Posthuman and Relational Approaches: Bringing Dualist Ontology, Cuts, and Relations in Legal Research - Walckiers, Pierre (Interconnections / Interconnexions, 2026)
This contribution introduces posthuman and relational theories as a critical methodological approach to law. Situated at the intersection of critiques of Western humanism and anthropocentrism, posthuman legal approaches challenge power dynamics both among humans and between humans and non-humans, extending the critique of law as objective, neutral, and detached from social context. By also critiquing the dualist ontology of law, which operates through ontological separations (between humans and non-humans, subject and object), posthuman approaches provide a framework to develop relational theory. Following an overview of the philosophical foundations of posthuman and relational approaches, as well as their methods for legal analysis, this article explores how these theories enable a better mapping of the interactions between human and non-human entities in law by examining relational continuums.